Acquired Activated Protein C Resistance, Thrombophilia and Adverse Pregnancy Outcomes: A Study Performed in an Irish Cohort of Pregnant Women - Sara Sedano-Balbás; Mark Lyons; Brendan Cleary; Margaret Murray; Geraldine Gaffney; Majella Maher (Journal of Pregnancy)
The combination of thrombophilia and pregnancy increases the risk of thrombosis and the potential for adverse outcomes during pregnancy. The most significant common inherited risk factor for thrombophilia is activated protein C resistance (APCR), a poor anticoagulant response of APC in haemostasis, which is mainly caused by an inherited single-nucleotide polymorphism (SNP), factor V G1691A (FV Leiden) (FVL), referred as inherited APCR. Changes in the levels of coagulation factors: FV, FVIII, and FIX, and anticoagulant factors: protein S (PS) and protein C (PC) can alter APC function causing acquired APCR. Prothrombin G20210A and methylenetetrahydrofolate reductase (MTHFR) C677T are prothrombotic SNPs which in association with APCR can also increase the risk of thrombosis amongst Caucasians. In this study, a correlation between an acquired APCR phenotype and increased levels of factors V, VIII, and IX was demonstrated. Thrombophilic mutations amongst our acquired APCR pregnant women cohort are relatively common but do not appear to exert a severe undue adverse effect on pregnancy.